Hospitalization outcomes among older adults living undiagnosed or unaware of dementia - Halima Amjad; Vishaldeep K. Sekhon; Jennifer L. Wolff; Quincy M. Samus; David L. Roth (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Many persons with dementia are undiagnosed or unaware of dementia, which may affect hospitalization outcomes. METHODS We evaluated differences in length of stay, days not at home, discharge destination, and 30‐day readmissions over 1 year in 6296 older adults in the National Health and Aging Trends Study with linked Medicare claims. Multivariable‐adjusted models compared outcomes across no dementia, undiagnosed dementia, unaware but diagnosed with dementia, and aware and diagnosed with dementia. RESULTS Persons with undiagnosed dementia had longer length of stay and were more likely to be discharged to a facility (44.8% vs. 19.3%) compared to no dementia; differences persisted in multivariable models. Persons undiagnosed or unaware experienced outcomes similar to persons aware and diagnosed except for more 30‐day readmissions in the undiagnosed (adjusted odds ratio [95% confidence interval] 2.05 [1.01, 4.16]). DISCUSSION Persons undiagnosed or unaware of dementia experience worse hospitalization outcomes, suggesting potential clinically significant implications of unrecognized dementia. Highlights Persons with undiagnosed versus no dementia have worse hospitalization outcomes. Persons with undiagnosed dementia have more 30‐day readmissions compared to persons diagnosed. Lack of clinician or family recognition of dementia may adversely affect hospitalization outcomes.